Implementation of the Least Square Method for The Application of Population Growth Rate Prediction in Air Sugihan District - Rizqi Prasetyo; Andri Andri; Susan Dian Purnamasari; Febriyanti Panjaitan (Universitas Bina Darma, 2022)
Air Sugihan is one of the 18 sub-districts in Ogan Komering Ilir Regency, South Sumatra Province which has 19 villages. After observation, in the annual program policy planning carried out by the Air Sugihan District, almost all development plans need to have an information base for future time estimates, namely predictions of population growth rates. Therefore, this study aims to contribute to the Air Sugihan sub-district by conducting a predictive analysis of the population growth rate with the least square method and implementing it into an application. The use of the least square method is a suitable method for predicting the rate of population growth. From the results of the analysis of prediction calculations for 2021, the same results were obtained with the details of the birth value of 762 with MAD errors (77.04) and MAPE (11.78 %), the death value of 460 with MAD errors (65.41) and MAPE (20.41 %), the Migration-coming value of 637 with MAD errors (190.67) and MAPE (81.55 %) and the Migration-away value of 877 with errors MAD (169.99) and MAPE (45.35 %). With the implementation into the application, it facilitates the process of managing population growth rate data in determining the results of predictions or forecasting and conclusions can be drawn from the prediction results for which factors or variables are more specific to affect the rate of population growth in the future.